Women of World War II : the untold stories [videorecording (DVD)]. (PBS, 2025)
American women were the secret weapon that won World War II and in the process, changed the world. Hear directly from the women who made the planes, and flew them; who fought on the warfront, and the home front; who broke codes and broke barriers.